Aspek Hukum Rekam Medis atau Rekam Medis Elektronik sebagai Alat Bukti Dalam Transaksi Teurapetik - Sudjana, Sudjana (Faculty of Law, Parahyangan Catholic University, 2017)
This study aims to obtain information on: first, the obligation to create and conceal Electronic Medical Record and its juridical consequences; Secondly, due to the law of absence or error in the manufacture of Electronic Medical Records and the position of Electronic Medical Record as a tool in the theoretical transactions.The research method used is normative juridical approach method, analytical descriptive research specification, research phase is done through literature study to examine primary law material, secondary law material, and tertiary law material. Data collection techniques are conducted through document studies, conducted by reviewing documents on positive law. Furthermore, the method of data analysis is done through normative qualitative.The results of the study indicate: Legal aspects of Medical Record or Electronic Medical Record in Teurapetik Transactions related to: first, the obligation of health workers in coaching and health services to make Medical Record or Electronic Medical Record correctly and responsible for secrecy because it is the opening of Medical Record or Electronic Medical Record without With the permission of the patient having the consequences of criminal law. The absence or misuse of the Medical Record or Electronic Medical Record means that health workers may be subject to criminal, civil and administrative sanctions. Second, the position of Medical Record or Electronic Medical Record is evidence in the form of a letter (if given outside the court), and expert information (if delivered in court).